Estudo do uso de fungos filamentosos como biocatalisadores para a produção de biodiesel e avaliação de alguns parâmetros reacionais - Norma Patricia Duran Osorio (2018)
The use of biocatalysts for biodiesel production is currently a promissory alternative to help resolve the most common problems associated with the conventional route. The filamentous fungi are nowadays the main source producing lipases to be used asbiocatalysts in the transesterification reaction. The lipases are quite attractive for their versatility and the wide variety of substrates that are capable of biotransform. One of the ways to use these biocatalysts is through its full cell with its active enzymatic machinery and which can be excreted to the cultivation medium where the fungus develops orretained in the mycelium (biomass). The purpose of this work was to select from a set of filamentous fungi those with greater capacity to be used as biocatalysts in the reaction of transesterification of soybean oil with mixture of methanol/ter-butyl alcohols compared to 1:1. First, seven filamentous fungi were chosen of which species were selected the fungiSyncephalastrum racemosum, Rhizopus stolonifer and Rhizopus oryzae. These have presented more promising results to be used with biocatalysts. They were evaluated in the form of biocatalyst present in the culture medium where the microorganism developed (lipase extracellular) and in the form of biocatalyst present in the full cell (biomass-lipase intracellular). Subsequently, the best reactional conditions were evaluated for the production of biodiesel for fungi Syncephalastrum racemosum and Rhizopus stolonifer.The following variables were studied: reaction time, molar ratio oil/alcohol, water content and quantity of biocatalyst presenting satisfactory results in 72 hours, molar ratio oil/alcohol 1:6, biocatalyst quantity 0.3 grams and water content 5% m/m. For Syncephalastrum racemosum were obtained yields of ester content of 37.15% using it inmixed in the middle of Cultrura and 85.5% in its form of integral cell. For the fungus Rhizopus stolonifer the yields were 27.2% and 52% respectively for the same conditions. Statistical tools were used in the evaluation of information as factorial planning and response surface methodology and the data analyzed through statistical packageStatistics 8.